(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Dreams have fascinated humans for centuries, serving as a bridge between the conscious and unconscious mind. This article explores the significance of dreams in both literature and psychology, examining how they reflect inner desires, fears, and conflicts. Drawing on classic literary examples and psychological theories from Freud, Jung, and contemporary research, the paper highlights the universal role dreams play in understanding human nature and creativity.